Financing of Church Activities - Iliev, Petkan (Research Papers, 2020)
The typology of "church-state" relationships is expressed in two basic approaches to religious activities: at the first, a given church / confession, religion is legally proclaimed by the state as sole or domineering, and the religion concerned is recognized as official. In this case, the official church is a monopolist in the religious services market; with the second approach, the state admits multi-contingency, ie. diversity of religions in society without official support of any of them, which can be perceived not as perfect competition but as monopolistic competition. This largely reflects on the ways in which the activities of religious institutions are financed through the so-called church tax (European practice) or the granting of tax incentives / reliefs (US practice), which is analyzed in this report.